Structure of Epistemology and Sufism Patterns on Malay-Jawi Interpretation: The Case of Q.S. Al-Fatihah Interpretation in Nurul Ihsan by Said bin Umar, Kedah - Wendi Parwanto (Program studi Keagamaan Islam, 2022)
Intellectual relationships and domicile can influence shaping a person's mindset. Including Said bin Umar is a scholar who concentrates on Sufism or tarekat. Therefore, it is essential to explore its interpretation when interpreting Q.S. al-Fatihah, because there could be nuances of the esoteric-Sufistic interpretation carried out by Said bin Umar. This research is a type of library research with the formal object of Tafsir Nurul Ihsan by Said bin Umar, and the material object is the interpretation of Q.S. al Fatihah. The conclusion of this article explains that Said bin Umar internalized his esoteric-Sufistic interpretation when interpreting verse 1 (basmalah) and verse 5 of Surah al-Fatihah. As for the factors that shape the emergence of esoteric-Sufistic reasoning, Said bin Umar when interpreting Q.S. al-Fatihah, are 1) The intellectual relationship of his teachers, 2) Anthropic-social configuration before and during comment writing, and 3) Relationships and tendencies of other literary with a written interpretation.